Visualizing Our Options for Coastal Places: Exploring Realistic Immersive Geovisualizations as Tools for Inclusive Approaches to Coastal Planning and Management - Newell, Robert; Canessa, Rosaline; Sharma, Tara (Frontiers in Marine Science, 2017)
Effective coastal planning is inclusive and incorporates the variety of user needs, values and interests associated with coastal environments. Realistic, immersive geographic visualizations, i.e., geovisualizations, can serve as potentially powerful tools for facilitating such planning because they can provide diverse groups with vivid understandings of how they would feel about certain management outcomes or impacts if transpired in real places. However, the majority of studies in this area have focused on terrestrial environments, and research on applications of such tools in the coastal and marine contexts is in its infancy. The current study aims to advance such research by examining the potential a land-to-sea geovisualization has to serve as a tool for inclusive coastal planning efforts. The research uses Sidney Spit Park (BC, Canada) as a study site, and a realistic, dynamic geovisualization of the park was developed (using Unity3D) that allows users to interact with and navigate it through the first-person perspective. Management scenarios were developed based on discussions with Parks Canada, and these scenarios included fencing around vegetation areas, positioning of mooring buoys, and management of dog activity within the park. Scenarios were built into the geovisualization in a manner that allows users to toggle different options. Focus groups were then assembled, involving residents of the Capital Regional District (BC, Canada), and participants explored and provided feedback on the scenarios. Findings from the study demonstrate the geovisualization’s usefulness for assessing certain qualities of scenarios, such as aesthetics and functionality of fencing options and potential viewshed impacts associated with different mooring boat locations. In addition, the study found that incorporating navigability into the geovisualization proved to be valuable for understanding scenarios that hold implications for the marine environment due to user ability to cross the land-sea interface and experience underwater places. Furthermore, this research demonstrated that building scenarios within a realistic geovisualization required modelling place-based characteristics (including soundscape) as well as spatial properties. This approach can allow users the ability to more comprehensively assess scenarios and consider potential options.